Determination of health status perception and orthorexia nervosa tendencies of Turkish yoga practitioners: a cross-sectional descriptive study - Erkin, Özüm; Göl, Ilknur (Progress in Nutrition, 2019)
As part of the yoga the possibility that excessive attention paid by practitioners to diet and food quality is expected. This study was aimed to determine health status perception and orthorexia nervosa tendencies of yoga practitioners. This cross-sectional descriptive study was conducted at three yoga centers in Izmir. The population of the study consisted of 153 people registered in yoga centers between March and May 2017. The data were collected using a personal information form (11 questions), Perception of Health Status Scale and Orthorexia Nervosa (Orto-11) Scale. While perceived physical health was “good” for 68.0% of the participants, the mean perceived health score was 1.94Å}0.54. The mean score of Orto-11 Scale was 24.05Å}4.36. It was determined that the perceived health of those who were married and non-smoker were higher than the orthorexia tendencies of the individuals who were married and had the chronic illness (p